High‐pressure‐induced phase transition and amorphization of xylitol by Raman spectroscopy. (13th December 2022) - Zhang, Shengya; Fang, Wenhui; Li, Fengjiao; Zhao, Bo; Men, Zhiwei
Abstract: Creating high‐pressure environments is an indispensable method to explore structural change, stability, and the upper limits for the application of xylitol under extreme conditions. Herein, we report a detailed description of the vibrations and phase transition of xylitol under high pressures by Raman spectroscopy. We found a novel phase transition of xylitol under 8.07 GPa by changing the O–H and CH2 vibrations. As the pressure further increased, xylitol underwent an amorphous transformation at 16.94 GPa. This study opens a new research perspective for polyols and expands the application of xylitol under extreme conditions. Abstract : The high‐pressure behavior of xylitol is studied by Raman spectroscopy, which will undergo phase transition and amorphization at 8.07 and 16.94 GPa, respectively. The characteristic Raman peak of O–H vibration disappeared after the phase transition. The main vibration modes of amorphous were the C–C, C–C–O, CH2, and C–O.